Computational screening of plant-derived compounds identifies Inophyllum E as a strong inhibitor of pancreatic lipase - Sayyid, Fatima; Ahmad Nadzirin, Izzuddin; Abdul Hamid, Azzmer Azzar; Alias, Norsyuhada (IIUM Press, 2025)
Introduction: Obesity is a chronic, multifactorial disease that imposes a significant global health burden. Inhibition of pancreatic lipase, a key enzyme in dietary fat absorption, is a validated therapeutic strategy. Orlistat, the only FDA-approved pancreatic lipase inhibitor, is limited by gastrointestinal side effects, prompting the search for safer, plant-derived alternatives.